Writing for Others in South Africa's Truth and Reconciliation Commission. Issue 2 (3rd May 2020) - Fleckstein, Anne
Abstract: Truth Commissions are a global transitional justice instrument for dealing with past atrocities. The South African Truth and Reconciliation Commission, active from 1996 to 2002, is regarded to be an influential role model in this field for the way it put an emphasis on the publicity of the process. However, it also established a temporary, complex administration which processed many more cases of human rights violations than were publicly heard or seen. This led to the perception of two separate operative spheres: While the public proceedings were dominated by oral speech, the non-public procedures tended to be in written form. In order to establish institutional authority within the TRC, procedures that implemented triadic structures (like advocacy, representation, parrhesia, or translation) were of particular significance. One central operative feature emerged from the first encounter that a witness of human rights violations would have with the TRC when giving a statement: the situation of a statement taker writing down the oral statement given by a witness. The article claims that this transmission of oral knowledge is a specific variation of "advocacy" and could be termed "writing-for." It amalgamates the triadic nature of advocacy (Campe) with the specific media technology of writing something down. The triad consists of the witness, the statement taker, and the statement form. The statement taking scene relied on a well-known aspect of the South African juridical administration, which is the Commissioner of Oaths. By adopting specific features of the Commissioner of Oaths and of affidavits, the testimony and the TRC gained authority. "Writing for others" served as a political form of care-taking, and authorized both the temporary institution and the testimony of the witness.